Diagnosis of the Situation of the Land Administration System in Ibero-America - Carmen Femenia-Ribera; Gaspar Mora-Navarro; Inmaculada Marques-Perez; Enric Terol; Cristhian Quiza-Neuto (Land, 2025)
In this research, we have compiled and analysed the organisations and studies that jointly address the issue of land administration, fundamentally in the cartographic aspects related to the cadastre and land registry, in the international environment, and at the Ibero-American level. Through qualitative social research, interviews were conducted with internationally recognised experts on issues of general cartography, cartography and legal security, and related to cadastral valuation, obtaining conclusions that allow a general diagnosis of the situation of the Land Administration System in Ibero-America. In this environment, problems such as the heterogeneity of systems, overlapping of competencies, instability, lack of sustainability, need for standards, lack of transparency, etc., should be highlighted, among others. Finally, based on the compilation of existing data from the Cadastre Data survey conducted in 2011 by the Permanent Committee of Cadastre in Ibero-America, and with information from its members and member organisations of the Pan-American Association of Professional Surveyors, the geoportal Diagnosis of the Situation of the Land Administration System in Ibero-America has been created. This geoportal allows the initial identification of the different organisations and general regional data.